Miksi keminsaame kuoli? - Valtonen, Taarna (Finland, 2026)
Kemi Saami is an extinct language that was spoken in the administrative region of Kemi Lapmark in present-day Northern Lapland, Finland. This article analyzes the sociolinguistic processes that resulted in the extinction of Kemi Saami. The analysis is based on contemporary descriptions from the eighteenth and nineteenth centuries. The information preserved in the descriptions is analyzed using the sociolinguistic analysis template developed under the European Language Diversity for All (ELDIA) project, as well as UNESCO’s nine factors describing the situation of an endangered language. The theoretical background is based on Joshua Fishman’s work on language shift. The results show that the extinction of Kemi Saami was a consequence of the language’s weak social status, the church’s language policy, and several social and cultural dislocations that the language community experienced. The most significant of these dislocations was the arrival of Finnish settlers and the agrarian socioeconomic model. The resulting population growth and environmental changes forced the inhabitants to give up the old way of life based on hunting and fishing. This led further to the deterioration of the socioeconomic situation of the language community in relation to the settlers and to the rapid weakening of cultural self-esteem. As a result, the members of the language community began to be ashamed of their own language and culture and wanted to give them up for Finnish language and culture.
Suomalais-Ugrilaisen Seuran Aikakauskirja